2019
DOI: 10.3989/ris.2019.77.2.18.052
|View full text |Cite
|
Sign up to set email alerts
|

El papel de las redes familiares en las decisiones de inmovilidad espacial en el área metropolitana de Granada

Abstract: Pese a que la familia es una reconocida institución con influencia en múltiples facetas de la vida social en España, no existen muchos estudios específicos sobre su papel en las trayectorias residenciales. Utilizando una encuesta realizada en el área metropolitana de Granada en 2008, en este trabajo analizamos la influencia de dos aspectos —la concentración de la red familiar y la presencia de raíces en el barrio— en las decisiones de movilidad e inmovilidad espacial. Los resultados indican que las redes famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
3
0
3
Order By: Relevance
“…This finding emphasizes that family and friends who live close by are experienced as constraints, and should be understood as a motivation for immobility. This is in line with earlier findings on the role of social ties determinants for staying behaviour in Spain (Clark et al, 2017 ; Palomares et al, 2019 ) as well as other contexts (Schewel & Fransen, 2022 ). While we did not formulate any hypotheses about this, those whose family and friends lived close by were also less likely to report ties to work.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This finding emphasizes that family and friends who live close by are experienced as constraints, and should be understood as a motivation for immobility. This is in line with earlier findings on the role of social ties determinants for staying behaviour in Spain (Clark et al, 2017 ; Palomares et al, 2019 ) as well as other contexts (Schewel & Fransen, 2022 ). While we did not formulate any hypotheses about this, those whose family and friends lived close by were also less likely to report ties to work.…”
Section: Resultssupporting
confidence: 93%
“…We observed that many of the self-reported constraints to migration involved sources of non-transferable capital (i.e., local ties) that have previously been shown to act as constraints to migration (David et al, 2010 ; Michaelides, 2011 ; Mulder & Malmberg, 2014 ; Palomares-Linares, 2018 ; Thomassen, 2021 ) and financial constraints (Landale & Guest, 1985 ; Sjaastad, 1962 ). Some examples are ‘family care obligations’, ‘a fear of change’, ‘the work location’, or feeling ‘happy here’; obstacles such as age or health; and financial limitations such as ‘income’.…”
Section: Appendix 1: Operationalisation Of Self-reported Constraints ...mentioning
confidence: 81%
See 1 more Smart Citation
“…For older adults, the anchor role of children is related to needs for proximity: geographical divergence between older parents and their adult children was less likely after the onset of parental formal care needs (Artamonova & Syse, 2021). ‘Staying practices’ in Granada were not only shaped by household circumstances and trajectories but are also connected to the geographies of social and family networks (Palomares‐Linares et al, 2016). The quality of the family relationship may also play a role.…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…No obstante, la importancia de la familia como factor de arraigo espacial es mayor entre las clases con menos recursos, así como en los barrios más desfavorecidos (Palomares-Linares et al, 2019). Al respecto, van Groenou y van Tilburg ( 2003) explican que las familias tienen necesidades de apoyo desiguales, así como desiguales son sus oportunidades de obtener bienestar fuera de las redes familiares.…”
Section: Proximidad Espacialunclassified